Часопростір в образотворчому мистецтві й літературі: експериментувати не можна спростити (контекст doppelbegabungen) - Moczerniuk, Natalia (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The article deals with the issue of the chronotope distinguishing features both in literature and in fine arts. The artists' attempts to include the category of time into painting and their speculations on the problem have been highlighted in the paper. Such concepts as sujet and rhythm, their relevance to fine arts have been brought into focus. Being a part of a principal study of the writers-artists’ oeuvres, the current paper contains the collected data on the painters’ transition from fine arts as a spatial one to literature. Their conversion to a new artistic field was caused by the desire to create temporal art and experiment with artistic time continuum.